Alleviating effects of coenzyme Q10 supplements on biomarkers of inflammation and oxidative stress: results from an umbrella meta-analysis - Dabbaghi Varnousfaderani, Sara; Musazadeh, Vali; Ghalichi, Faezeh; Kavyani, Zeynab; Razmjouei, Soha; Faghfouri, Amir Hossein; Ahrabi, Sana Sedgh; Seyyed Shoura, Seyyed Morteza; Dehghan, Parvin (Frontiers in Pharmacology, 2023)
Although several meta-analyses support the positive effect of coenzyme Q10 (CoQ10) on biomarkers of oxidative stress and inflammation, the results of some other studies reject such effects. Therefore, in this umbrella meta-analysis, we performed a comprehensive systematic search in such databases as Web of Science, PubMed, Scopus, Embase, and Google Scholar up to January 2023. Based on standardized mean difference (SMD) analysis, CoQ10 supplementation significantly decreased serum C-reactive protein (CRP) (ESSMD = -0.39; 95% CI: -0.77, -0.01, p = 0.042) and malondialdehyde (MDA) (ESSMD = -1.17; 95% CI: -1.55, -0.79, p < 0.001), while it increased the total antioxidant capacity (TAC) (ESSMD = 1.21; 95% CI: 0.61, 1.81, p < 0.001) and serum superoxide dismutase (SOD) activity (ESSMD = 1.08; 95% CI: 0.37, 1.79, p = 0.003).However, CoQ10 supplementation had no significant reducing effect on tumor-necrosis factoralpha (TNF-α) (ESSMD = -0.70; 95% CI: -2.09, 0.68, p = 0.320) and interleukin-6 (IL-6) levels (ESSMD = -0.85; 95% CI: -1.71, 0.01, p = 0.053). Based on weighted mean difference (WMD) analysis, CoQ10 supplementation considerably decreased TNF-α (ESWMD = -0.46, 95% CI: -0.65, -0.27; p < 0.001), IL-6 (ESWMD = -0.92, 95% CI: -1.40, -0.45; p < 0.001), and CRP levels (ES WMD = -0.28, 95% CI: -0.47, -0.09; p < 0.001). The results of our meta-analysis supported the alleviating effects of CoQ10 on markers of inflammation cautiously. However, CoQ10 had antioxidant effects regarding the improvement of all the studied antioxidant and oxidative stress biomarkers.